2008
DOI: 10.1016/j.physleta.2008.08.065
|View full text |Cite
|
Sign up to set email alerts
|

Spin magnetosonic shock-like waves in quantum plasmas

Abstract: The one-dimensional shock structures of magnetosonic waves (MSWs) propagating in a dissipative quantum plasma medium is studied. A quantum magnetohydrodynamic (QMHD) model is used to take into account the quantum force term due to Bohm potential and the pressure-like spin force term for electrons. The nonlinear evolution (Korteweg de-Vries-Burger ) equation, derived to describe the dynamics of small amplitude MSWs, where the dissipation is provided by the plasma resistivity, is solved numerically to obtain bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…18 Nonlinear collective processes in quantum plasmas have been investigated by including both quantum tunneling and electron spin effects on an equal footing, which can give rise to new collective linear and nonlinear magnetosonic excitations, 19 such as solitons, 20,21 localized whistlers, 22 and shock waves. 23 The effect of electron spin on magnetosonic waves can be incorporated via the spin force and macroscopic spin magnetization current. In electron-positron pair plasmas, the microscopic spin properties can also give rise to new Alfv enic solitary waves which do not exist if the quantum spin effects are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…18 Nonlinear collective processes in quantum plasmas have been investigated by including both quantum tunneling and electron spin effects on an equal footing, which can give rise to new collective linear and nonlinear magnetosonic excitations, 19 such as solitons, 20,21 localized whistlers, 22 and shock waves. 23 The effect of electron spin on magnetosonic waves can be incorporated via the spin force and macroscopic spin magnetization current. In electron-positron pair plasmas, the microscopic spin properties can also give rise to new Alfv enic solitary waves which do not exist if the quantum spin effects are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…In their work they found that if one neglects the magnetic diffusivity, the magnetic field satisfies an equation identical to the equation of continuity and hence one can take the magnetic field linearly proportional to the density of plasma fluid by applying the simplification of the governing equations. Later Misra and Ghosh (2008) obtained the spin magnetosonic shock like waves in quantum plasma, where they took account of magnetic diffusivity, using the reductive perturbation technique. Very recently, linear and nonlinear compressional magnetosonic waves in magnetized degenerate spin-1/2 Fermi plasmas are also investigated (Mushtaq and Vladimirov 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the latter has been recognized in the context of plasmonics, 16 in quantum wells, 17 in ultracold, 18 and astrophysical plasmas. 19 Various collective phenomena in dense quantum plasmas have been investigated, where the Bohm de Broglie potential and the Fermi pressure, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] spin properties, 27,[29][30][31][32][33]35 as well as certain quantum electrodynamical effects 36,37 are accounted for.…”
Section: Introductionmentioning
confidence: 99%